Effects of mobile phone emissions on human red blood cells. Issue 8 (25th May 2021) - Chowdhury, Aniket; Singh, Yashveer; Das, Uttam; Waghmare, Deepak; Dasgupta, Raktim; Majumder, Shovan Kumar
Abstract: Raman spectroscopy was performed on GSM 900 and 1800 MHz mobile phone signal exposed red blood cells (RBCs). The observed changes in the Raman spectra of mobile signal exposed RBCs compared to unexposed control suggest reduced hemoglobin‐oxygen affinity for the exposed cells. The possible mechanism may involve activation of the voltage gated membrane Ca 2+ channels by the mobile phone emissions resulting in an increase in the levels of adenosine triphosphate (ATP) and 2, 3‐diphosphoglycerate (2, 3‐DPG) in cells via altered metabolic activities. Further studies carried out with fluorescent Ca 2+ indicator confirmed increased intracellular Ca 2+ level in the exposed cells. Since intracellular ATP level influences the shape and mechanics of RBCs, exposed cells were studied using diffraction phase microscopy and optical tweezers. Detectable changes in shape and mechanical properties were observed due to mobile signal exposure. Abstract : The use of mobile phones is now widespread but possible health hazards from the associated microwave emission are merely understood. The results of our studies, using single cell Raman spectroscopy on the effects of 900 and 1800 MHz mobile signals on human red blood cells, show a reduction in oxygen affinity of the cells upon exposure. Assuming the mobile signals may influence the membrane transport of calcium ions and subsequently the metabolic processes, further studies using fluorescent probes and quantitative phase microscopy were performed and the results support the suggested mechanism.